The Effect of Family-to-Work Conflict and Job Satisfaction on Job Performance among Pussenkav Personnel (Pussenkav TNI AD) - Windi Ayu Setianingrum; Rima Rahmayanti (CV. Radja Publika, 2026)
This study aims to examine the effects of Family-to-Work Conflict and Job Satisfaction on Job Performance, with Emotional Exhaustion serving as a mediating variable among personnel of the Indonesian Army Cavalry Center (Pusat Kesenjataan Kavaleri/Pussenkav). A quantitative explanatory research design was employed. Data were collected through a structured questionnaire distributed to 170 respondents selected using proportional stratified random sampling from a population of 295 personnel. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that Job Satisfaction has a positive and significant effect on Job Performance (β = 0.823, p < 0.001) and Emotional Exhaustion (β = 0.132, p = 0.033). Family-to-Work Conflict has a positive and significant effect on Emotional Exhaustion (β = 0.720, p < 0.001), but does not significantly affect Job Performance (β = 0.050, p = 0.554). Furthermore, Emotional Exhaustion has no significant effect on Job Performance (β = –0.031, p = 0.731) and does not mediate the relationships between Family-to-Work Conflict and Job Performance, or between Job Satisfaction and Job Performance. These findings suggest that job satisfaction is the primary determinant of personnel performance, while family-related conflict and emotional exhaustion do not directly impair job performance within the highly disciplined and professional military organizational context.